2022
DOI: 10.3390/cells11121912
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Immune Cell Activation in Pemphigus

Abstract: (1) Background: Pemphigus is a blistering autoimmune disease of the skin and/or mucous membranes, characterised by the presence of specific autoantibodies directed against structural proteins of the human skin. Recent reports indicate that new haematological parameters, termed Extended Inflammation Parameters (EIP), can be used to assess the activation of immune cells during active inflammation. These include parameters assessing both neutrophil activation (NEUT-RI, NEUT-GI) and the number of activated lymphoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
1
5
0
1
Order By: Relevance
“…Interestingly, our transcriptome results showed IL-8, IL-19, IL-17A, IL-17F, IL-1B, S100A9, S100A12, S100A8, and IL-23A to be the top upregulated immune markers. Furthermore, cell profiling enrichment revealed the activation of T cells, CD45 cells, and neutrophils in lesional canine PF samples; the activation of these types of cells corresponds to the histopathological features of canine PF and has been previously reported in human and canine pemphigus [15][16][17]. Several chemokines and chemokine receptors (i.e., IL-8 (CXCL8), CCL3, CCL4, CCL8, CCL20, CCL28, and CXCL10) that could contribute to the immune infiltration of immune cells in skin lesions displayed strong gene expression upregulation in canine PF lesions.…”
Section: Discussionsupporting
confidence: 65%
“…Interestingly, our transcriptome results showed IL-8, IL-19, IL-17A, IL-17F, IL-1B, S100A9, S100A12, S100A8, and IL-23A to be the top upregulated immune markers. Furthermore, cell profiling enrichment revealed the activation of T cells, CD45 cells, and neutrophils in lesional canine PF samples; the activation of these types of cells corresponds to the histopathological features of canine PF and has been previously reported in human and canine pemphigus [15][16][17]. Several chemokines and chemokine receptors (i.e., IL-8 (CXCL8), CCL3, CCL4, CCL8, CCL20, CCL28, and CXCL10) that could contribute to the immune infiltration of immune cells in skin lesions displayed strong gene expression upregulation in canine PF lesions.…”
Section: Discussionsupporting
confidence: 65%
“…The measurement takes into account the metabolic activity of neutrophils, the internal structure and the size of the cell [ 7 ]. It was revealed that these parameters can be used in diseases of various aetiology, such as psoriasis [ 8 ], pemphigus [ 9 ], type II diabetes, and gynaecological diseases (endometriosis, uterine fibroids) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…6 The parameter was proposed as an early marker of infection and sepsis, [6][7][8] a risk marker of mechanical ventilation during Coronavirus disease 2019 9,10 as well as a marker of autoimmune disease. [11][12][13] The normal level of NEUT-RI in samples without pathology was documented to be 45.4 fluorescence intensity (FI) with a standard deviation of 2.8 FI. 6 In cases where part of a dense IG tail is misinterpreted as part of the mature neutrophil population, the NEUT-RI rises as a result of the higher mean fluorescence signal.…”
Section: Introductionmentioning
confidence: 99%
“…NEUT‐RI corresponds to the NEUT‐Y value in the Sysmex XE‐series and represents the neutrophil reactivity and metabolic activity expressed by the mean fluorescent signal of the neutrophil population 6 . The parameter was proposed as an early marker of infection and sepsis, 6–8 a risk marker of mechanical ventilation during Coronavirus disease 2019 9,10 as well as a marker of autoimmune disease 11–13 . The normal level of NEUT‐RI in samples without pathology was documented to be 45.4 fluorescence intensity (FI) with a standard deviation of 2.8 FI 6 .…”
Section: Introductionmentioning
confidence: 99%